Examining the levels of psychological support available to patients with haematological cancer in England: a mixed methods study. Issue 2 (20th February 2023) - Brett, Jo; Henshall, Catherine; Dawson, Paul; Collins, Graham P; Ehlers, Anke; Mitchell-Floyd, Tracy; Aspinall, Anya; Gilmour-Hamilton, Catriona; Robinson, Kate; Watson, Eila
Abstract : Objectives: The psychological impact of a haematological malignancy is well documented. However, few studies have assessed the provision of psychological support to people with these diagnoses. This study explores the extent and nature of psychological support for people diagnosed with haematological cancer to inform future service provision. Design: This study consisted of an online survey with healthcare professionals (phase 1) and qualitative interviews with patients (phase 2) and key health professionals (phase 3). A descriptive analysis of survey data and thematic analysis of interviews were conducted. Participants: Two hundred health professionals practising in England completed the survey. Twenty-five interviews were conducted with people diagnosed with haematological cancer in the past 3 years, and 10 with key health professionals, including haematologists, cancer nurse specialists and psychologists were conducted. Primary outcome measures: Level of psychological assessment undertaken with people with haematological cancer, and level and nature of psychological support provided. Results: Less than half (47.3%) of survey respondents strongly agreed/agreed that their patients were well supported in terms of their psychological well-being and approximately half (49.4%) reported providing routine assessment of psychological needs of patients, most commonly at the time of diagnosis or relapse. Patients described their need for psychological support, their experiences of support from health professionals and their experiences of support from psychological therapy services. There was considerable variation in the support patients described receiving. Barriers to providing psychological support reported by health professionals included time, skills, resources and patient barriers. Most doctors (85%) and 40% of nurse respondents reported receiving no training for assessing and managing psychological needs. Conclusions: Psychological well-being should be routinely assessed, and person-centred support should be offered regularly throughout the haematological cancer journey. Greater provision of healthcare professional training in this area and better integration of psychological support services into the patient care pathway are required.